Filipino LGBTQ+ Emerging Adults’ Conceptualization of Romantic Relationships - Cardona, Louis Miguel; Ancho, Inero; Vergara, Helga; Laude, Teri-Marie; Albor, Rufo Gil; Pelegrina, Daisy; Almeda, Phrygian (International Journal of Multidisciplinary Sciences, 2025)
This study investigates the narratives of contemporary romance among Filipino LGBTQ+ emerging adults, emphasizing their lived experiences, modern influences, and cultural determinants that form their relationships. A qualitative phenomenological design was employed to conduct semi-structured interviews with eight participants from a state institution in Laguna, Philippines. The findings indicated that romantic connections are crucial in identity exploration and self-affirmation. Participants characterized love as a collaboration founded on reciprocal respect, emotional intimacy, and equality, contesting established conventions and heteronormative standards. Digital platforms facilitated connections and provided safe spaces for users; nevertheless, they also engendered obstacles, including false expectations and superficial interactions. Cultural influences, including familial expectations and Catholic ideals, were substantial, offering both obstacles and avenues for growth and authenticity. This study offers insights into the interplay between identity, culture, and love; but, its limited sample size and concentration on a particular university restrict its generalizability. Future research ought to investigate many contexts, encompassing rural regions and a wider array of socioeconomic demographics, while analyzing the changing influence of technology on LGBTQ+ relationships. This study emphasizes the resilience of Filipino LGBTQ+ emerging adults and advocates for inclusive legislation and community assistance to foster acceptance and equality.